2016
DOI: 10.1186/s12944-016-0365-6
|View full text |Cite
|
Sign up to set email alerts
|

Fetal gender and gestational age differentially affect PCSK9 levels in intrauterine growth restriction

Abstract: BackgroundMaternal and fetal Low Density Lipoprotein-Cholesterol (LDL-C) concentrations are compromised in intrauterine growth restriction (IUGR). Generally, LDL-C catabolism is under control of PCSK9 by binding to the LDL-receptor leading to its degradation. Hence, we hypothesized a role for PCSK9 in the modulation of lipid metabolism and placental transport in IUGR.Methods172 women, 70 IUGR and 102 controls were included in the study. Maternal and fetal serum PCSK9 levels and lipid profiles including LDL-C w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
1
17
1
Order By: Relevance
“…LDLR and LDL uptake. LDLR was early described in the placenta 16,40 ; however, only two reports showed the in situ localization of LDLR in placental tissue 17,41 . In agreement with both papers, our confocal microscopy images of the whole placenta showed that LDLR was expressed mainly in the placental syncytiotrophoblast layer and suggest that the localization could be predominantly in the apical membrane, which requires confirmation with specific markers for this syncytiotrophoblast membrane in the same section of tissue.…”
Section: Discussionmentioning
confidence: 99%
“…LDLR and LDL uptake. LDLR was early described in the placenta 16,40 ; however, only two reports showed the in situ localization of LDLR in placental tissue 17,41 . In agreement with both papers, our confocal microscopy images of the whole placenta showed that LDLR was expressed mainly in the placental syncytiotrophoblast layer and suggest that the localization could be predominantly in the apical membrane, which requires confirmation with specific markers for this syncytiotrophoblast membrane in the same section of tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, including our own, have reported diminished fetal cholesterol concentrations in IUGR [1723]. Characterizing umbilical cord blood sterol profiles in IUGR and normally grown fetuses we aimed at a deeper understanding of cholesterol metabolism during fetal development and impaired fetal growth.…”
Section: Discussionmentioning
confidence: 99%
“…In IUGR, cholesterol concentration in fetal blood is low [1723]. In particular, the high-density lipoprotein (HDL) fraction, which is the main cholesterol acceptor and dominant lipoprotein in the fetus, is diminished by about 50% when compared to appropriately grown fetuses [17].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the diagnosis of IUGR is based ideally on the antenatal observation of a deceleration of fetal growth velocity by serial sonographic measurements showing a “crossing of percentiles” or other antenatal parameters of fetal well-being [ 22 , 36 ]. Evidence is increasing that IUGR is a heterogeneous disorder that can be subdivided into clinical presentation of concomitant preeclampsia and early onset or late onset IUGR with a cut-off at 32 to 34 weeks of gestation [ 2 , 37 ]. Both, preeclampsia and increased resistance of the umbilical arteries (as indicated by resistance index/pulsatility index in Doppler sonography) are often associated with severe early onset IUGR.…”
Section: Discussionmentioning
confidence: 99%